2023
DOI: 10.3390/dj11010024
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Orofacial Technology and Orthodontics

Abstract: Wearable technology to augment traditional approaches are increasingly being added to the arsenals of treatment providers. Wearable technology generally refers to electronic systems, devices, or sensors that are usually worn on or are in close proximity to the human body. Wearables may be stand-alone or integrated into materials that are worn on the body. What sets medical wearables apart from other systems is their ability to collect, store, and relay information regarding an individual’s current body status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 206 publications
0
2
0
Order By: Relevance
“…Currently, a comprehensive evaluation of the facial skeleton in conjunction with soft tissue proportions, skeletal features, teeth, and occlusion holds paramount importance in contemporary orthodontic treatment and orthognathic surgery protocols. Numerous advancements in orthodontic and orthognathic studies have been reported, as noted by Prasad et al [61] and Starch-Jensen et al [1]. The main findings suggest that new technologies in cephalometric assessment are the future, but significant efforts are needed to fully optimize their performance.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Currently, a comprehensive evaluation of the facial skeleton in conjunction with soft tissue proportions, skeletal features, teeth, and occlusion holds paramount importance in contemporary orthodontic treatment and orthognathic surgery protocols. Numerous advancements in orthodontic and orthognathic studies have been reported, as noted by Prasad et al [61] and Starch-Jensen et al [1]. The main findings suggest that new technologies in cephalometric assessment are the future, but significant efforts are needed to fully optimize their performance.…”
Section: Discussionmentioning
confidence: 97%
“…In turn, other factors, such as patient positioning, maintaining a good NHP, and ensuring appropriate resting positions of the jaw, teeth, facial features, skull, and body posture during examination, are areas that still warrant attention [1,61]. The most critical aspect of evaluating facial photographs, CBCT scans, and 3D assessments lies in achieving a natural, physiologically balanced head position and patient silhouette.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AI holds the potential to revolutionize the way patient follow-ups are conducted, using remotely obtained data from wearable devices or image sources (Prasad et al 2023). The application of AI in telemonitoring software has been positively received by both patients and dental practitioners alike (Dalessandri et al 2021).…”
Section: Applicationsmentioning
confidence: 99%
“…This wearable sensor's ability to track mandibular motion has demonstrated promise for both treating bruxism and diagnosing OSA. 3 The recent surge in diagnostic aids and treatment modalities has propelled orthodontics into a new era of precision, efficiency, and patient-centric care. These advancements underscore the commitment of the orthodontic community to staying at the forefront of innovation for the benefit of patients and the evolution of the field.…”
Section: Current and Emerging Uses Of Technology In Orthodontics 211 ...mentioning
confidence: 99%